Construção de tecnologia educacional sobre crenças e tabus alimentares no período gestacional - ARAÚJO, Aléxia Maria Santos (2023)
During the gestational period, several changes are experienced, both physiological, anatomical, and biochemical, as well as eating habits, due to beliefs and taboos, pregnant women deprive themselves of the consumption of important foods for their nutrition. Develop digital educational technology through scientific evidence on beliefs and food taboos to mediate food and nutrition education activities for pregnant women. The qualitative study was carried out through an integrative literature review, from October to November 2022, selection criteria: original articles published in English and Portuguese, between 2006 and 2022, available online and with adherence to the theme. Six articles were found in the following databases: Scielo, BVS, and ResearchGate. The study was described in two stages: the contextualization of educational technology and the development of the booklet. It was observed, according to the selected articles, that beliefs and food taboos are present in some periods, including the gestational period, which leads to some restrictions in food, such as proteins, citrus/bitter fruits, coffee, cinnamon, heavy food, and even behaviors like eating for two and pregnancy cravings. After structuring the results, the educational technology of the digital booklet type was elaborated, divided into introduction, pregnancy, healthy eating during pregnancy, nutrition, beliefs, and taboos. and food beliefs and taboos, with elements that facilitate reading, are easy to understand and have visual resources that are attractive to the reader. The importance of developing educational technology accessible to pregnant women to demystify these prejudices about beliefs and food taboos, improving the assistance of professional nutritionists in Primary Health Care in food and nutrition education that is adequate and safe for mother and baby.